Strategi Peningkatan Kompetensi Sumber Daya Manusia dalam Usaha UMKM Amplang di Pondok Pesantren Mambaul Khairot - Hariyanto, Hariyanto; Firayanti, Yuni; Marhamah, Marhamah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This research aims to analyze the strategies for improving human resource competencies in managing Micro, Small, and Medium Enterprises (MSMEs) based on pesantren, especially in the production of amplang at Pondok Pesantren Mambaul Khairat. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observations, and documentation. Data analysis employs qualitative data analysis with the stages of data reduction, data presentation, and drawing conclusions. The research results show that the strategy to improve human resource competencies is carried out through practice-based training (learning by doing), instilling work values such as discipline and responsibility, a regeneration system for students, and active participation in every production process. Supporting factors for business development include the social legitimacy of the pesantren, availability of local raw materials, community support, student motivation, and a simple marketing network. Nevertheless, the business still faces obstacles such as limited capital, simple production equipment, traditional marketing, weak management, and minimal external support. This study concludes that strengthening HR competencies and synergy with external support are the main keys to improving the competitiveness and sustainability of pesantren amplang SMEs.